Plasma medicine - Fridman, Alexander A., 1953-; Friedman, Gary (Gary G.) (Chichester, West Sussex, UK : John Wiley & Sons, 2013)
"This comprehensive text is suitable for researchers and graduate students of a 'hot' new topic in medical physics. Written by the world's leading experts, this book aims to present recent developments in plasma medicine, both technological and scientific, reviewed in a fashion accessible to the highly interdisciplinary audience consisting of doctors, physicists, biologists, chemists and other scientists, university students and professors, engineers and medical practitioners. The book focuses on major topics and covers the physics required to develop novel plasma discharges relevant for medical applications, the medicine to apply the technology not only in-vitro but also in-vivo testing and the biology to understand complicated bio-chemical processes involved in plasma interaction with living tissues"--Provided by publisher.
Introduction to fundamental and applied aspects of plasma medicine -- Fundamentals of plasma physics and plasma chemistry relevant to biological and medical applications -- Selected concepts in biology and medicine for physical scientists -- Major plasma disharges and their applicability for plasma medicine -- Mechanisms of plasma interactions with cells -- Plasma sterilization of different surfaces and living tissues -- Plasma decontamination of water and air streams -- Plasma treatment of blood : non-thermal plasma-assisted blood coagulation and plasma control of blood properties -- Plasma assisted healing and treatment of diseases -- Plasma pharmacology -- Fundamentals of plasma-assisted tissue engineering and plasma processing of polymers.
Includes index.
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
Keywords: Biomedical engineering; Plasma cells; Wound healing; Biomedical Engineering; Plasma Gases -- therapeutic use; Plasma Gases -- pharmacology; Wound Healing; MEDICAL -- Allied Health Services -- Medical Technology; MEDICAL -- Biotechnology; MEDICAL -- Family & General Practice; MEDICAL -- Lasers in Medicine; TECHNOLOGY & ENGINEERING -- Biomedical; Biomedical engineering; Plasma cells; Wound healing; Electronic books; Electronic books